2018
DOI: 10.3390/plants7040090
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of Wild Apple (Malus spp.) By-Products as a Source of Essential Fatty Acids, Tocopherols and Phytosterols with Antimicrobial Activity

Abstract: The amplified production of fruit as well as burgeoning demand for plant-made food products have resulted in a sharp increase of waste. Currently, millions of tons of by-products are either being discarded or utilized rather ineffectively. However, these by-products may be processed and further incorporated as functional ingredients in making high-value food products with many physiological and biochemical effects. The chemical analysis of pomace oils using gas chromatography-mass spectrometry (GC/MS) and reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 51 publications
4
22
1
Order By: Relevance
“…These results concerning the fatty acid composition of PL from apple juice and apple cider are in accordance with previously reported ones for lipids from apple juice and cider [22,23], but also in PL from other plant-derived food sources used for beverages products, such as beer and tea [9,17].…”
Section: Fatty Acid Composition Of Bioactive Pl From Apple Juices Andsupporting
confidence: 92%
“…These results concerning the fatty acid composition of PL from apple juice and apple cider are in accordance with previously reported ones for lipids from apple juice and cider [22,23], but also in PL from other plant-derived food sources used for beverages products, such as beer and tea [9,17].…”
Section: Fatty Acid Composition Of Bioactive Pl From Apple Juices Andsupporting
confidence: 92%
“…It was also reported that the presence of phloretin and its glycosylated derivatives in apples are able to inhibit growth of Gram-positive bacteria, and are active against some strains of the Gram-negative bacteria [ 48 ]. In the research of Radenkovs (2018) [ 49 ] wild apple pomace oil showed inhibitory capacity against both Gram-positive and Gram-negative bacteria strains. These could explain the antimicrobial activity of AppMPNF against Streptococcus epidermis and Streptococcus mutans found din our research data.…”
Section: Resultsmentioning
confidence: 99%
“…Each bran sample before EH was defatted following the methodology described by Radenkovs et al [ 25 ] and ground to reach Ø 0.5 mm particle size using a variable speed rotor mill Pulverisette 14 (Fritsch, Idar-Oberstein, Germany). To exclude possible cell-wall disruption by native enzymes and microorganisms that can be localized on the surface of bran, the samples were mixed with double distilled water (DDW) at the ratio of 1:10 ( w / v ), loaded into 25 mL reagent bottles with screw caps (VWR™, International, GmbH, Darmstadt, Germany), and subjected to autoclaving using a digital autoclave with counter-pressure (Raypa, AES 110, Barcelona, Spain) for 10 min at 121 ± 1 °C temperature and counter pressure 2.0 Pa.…”
Section: Methodsmentioning
confidence: 99%